A tale of two hedge funds : Magnetar and Peloton - Stowell, David (David P.); Carlson, Stephen (London : SAGE Publications Ltd, 2017)
Hedge fund Magnetar Capital had returned 25 percent in 2007 with a strategy that posed significantly lower risk to investors than the S&P 500. Magnetar had made more than $1 billion in profit by noticing that the equity tranche of CDOs and CDO-derivative instruments were relatively mispriced. It took advantage of this anomaly by purchasing CDO equity and buying credit default swap (CDS) protection on tranches that were considered less risky. Now it was the job of Alec Litowitz, chairman and chief investment officer, to provide guidance to his team as they planned next year's strategy, evaluate and prioritize their ideas, and generate new ideas of his own. An ocean away, Ron Beller was contemplating some very different issues. Beller's firm, Peloton Partners LLP, had been one of the top-performing hedge funds in 2007, returning in excess of 80 percent. In late January 2008 Beller accepted two prestigious awards at a black-tie EuroHedge ceremony. A month later, his firm was bankrupt. Beller shorted the U.S. housing market before the subprime crisis hit, and was paid handsomely for his bet. After the crisis began, however, he believed that prices for highly rated mortgage securities were being unfairly punished, so he decided to go long AAA-rated securities backed by Alt-A mortgage loans (between prime and subprime), levered 9x. The trade moved against Peloton in a big way on February 14, 2008, causing $17 billion in losses and closure of the firm.
Originally published: Stowell, D. P., & Carlson, S. (2009). A tale of two hedge funds: Magnetar and Peloton. 5-308-508. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Magnatar Capital (Firm) -- Case studies; Peloton Partners, LLP (Firm) -- Case studies; Hedge funds -- United States -- Case studies; Risk management -- United States -- Case studies; Investments -- Management -- United States -- Case studies; Hedge funds -- Great Britain -- Case studies; Risk management -- Great Britain -- Case studies; Investments -- Management -- Great Britain -- Case studies